Qualidade interna de ovos comerciais armazenados em refrigeradores domésticos - ARRUDA, Milena Raiane Silva de; SILVA, Giovana Seizer; BARONI, Thaís de Abreu Toledo; SANTOS, Thais Laine da Rocha; SERVIN, Zathia Rosa Soliz; GARCIA, Elis Regina de Moraes (ANAIS DO ENIC, 2025)
-